The Critical Thinking Skills and Scientific Attitudes of Pre-Service Chemistry Teachers Through the Implementation of Problem-Based Learning Model - Dwi Wahyudiati (Jurnal Penelitian Pendidikan IPA, 2022)
This study aims to determine the effect of applying problem-based learning models on critical thinking skills and scientific attitudes of pre-service chemistry teachers in Basic Chemistry 1. This quasi-experimental research uses pre-test and post-test through an unequal control group design. This research has been carried out for 3 months from September-November in 2021 on pre-service chemistry teachers. The data were analyzed using Hotelling's T2 test and the Rasch model. Empirical evidence shows that based on Hotelling's T2 test results obtained a significance value of 0.001 < (0.05) with a partial eta squared value of 0.28 which means Ha is accepted. So, it can be concluded that there is a contribution of problem-based learning models on critical thinking skills and scientific attitudes of students with the contribution of 28%. Another finding also shows that based on the results of the Rasch model test, it shows that in the experimental class the indicators of critical thinking skills and scientific attitudes are mostly possessed the ability to synthesize attitudes towards scientific investigations. The indicators of critical thinking skills and scientific attitudes are least possessed the ability to analyze and chemistry learning experiences. The conclusions of this study include there is a significant effect of the application of the PBL model on students' critical thinking skills and scientific attitudes with a model contribution of 28%, as well as critical thinking skills and scientific attitudes that most students have in the experimental class are analytical skills and attitudes towards scientific investigations.